Resisting occupation in Kashmir - Duschinski, Haley; Bhan, Mona; Zia, Ather; Mahmood, Cynthia Keppley (Ethnography of political violence., 2018)
"The last decade has been a transformative period in Kashmir, the contested, densely militarized border territory located in the Himalayan mountains between India and Pakistan. Suppressed and unheard, Kashmiri political aspirations were subordinated to larger geopolitical concerns--by opposing governments laying claim to Kashmir, by security experts promoting bilateral peace settlements in the region, and by academic researchers studying the conflict. But since 2008, Kashmiris who grew up in the midst of armed insurgency and counterinsurgency warfare have been deploying new strategies for challenging India's state and military apparatus and projecting their legal and political claims for freedom from Indian rule to global audiences. This book analyzes the social and legal logic of India's occupation of Kashmir in relation to colonialism, militarization, power, democracy, and sovereignty."--Publisher's description